Control of the robotic arm of six degrees of freedom, through visual feedback, for the harvest of paprika chili - Rodriguez B, Ricardo (2011)
The present document is the culmination of mechatronic interaction, between the computer vision and control of robot areas for automation process of paprika pepper's harvest. A robot of 6 DOF (degree of liberty) perform the process of harvest, this robot give to us more versatility in complex movements and operations on rural lands. To operate the movements and 3D positions of the robot we use a visual sensor and distance infrared sensor. The visual sensor gives us required images to recognize the environment, the sensor infrared measures the deep, and withthese two values we can obtain the specific location of the peppers in the robot's workspace.